On the inverse cascade and flow speed scaling behaviour in rapidly rotating Rayleigh–Bénard convection. (3rd March 2021) - Maffei, S.; Krouss, M.J.; Julien, K.; Calkins, M.A.
Abstract: Abstract : Rotating Rayleigh–Bénard convection is investigated numerically with the use of an asymptotic model that captures the rapidly rotating, small Ekman number limit, Ek → 0 . The Prandtl number ( Pr ) and the asymptotically scaled Rayleigh number ( Ra = Ra Ek^4/3, where Ra is the typical Rayleigh number) are varied systematically. For sufficiently vigorous convection, an inverse kinetic energy cascade leads to the formation of a pair of large-scale vortices of opposite polarity, in agreement with previous studies of rapidly rotating convection. With respect to the kinetic energy, we find a transition from convection dominated states to a state dominated by large-scale vortices at an asymptotically reduced (small-scale) Reynolds number of Re ≈ 6 ( Re = Re Ek^1/3, where Re is the Reynolds number associated with vertical flows) for all investigated values of Pr . The ratio of the depth-averaged kinetic energy to the kinetic energy of the convection reaches a maximum at Re ≈ 24, then decreases as Ra is increased. This decrease in the relative kinetic energy of the large-scale vortices is associated with a decrease in the convective correlations with increasing Rayleigh number. The scaling behaviour of the convective flow speeds is studied; although a linear scaling of the form Re Ra/Pr is observed over a limited range in Rayleigh number and Prandtl number, a clear departure from this scaling is observed at the highest accessible values of Ra . Calculation of the forces present in the governing equations shows that the ratio of the viscous force to the buoyancy force is an increasing function of Ra, that approaches unity over the investigated range of parameters.